Ethnographies of law and social control - Burns, Stacy Lee. (Amsterdam ; Boston : Elsevier JAI, 2005)
This volume brings together distinguished scholars and cutting-edge experts in the fields of ethnography, law, and social control to present a comprehensive, insightful, and state-of-the-art overview of the everyday work and activities of legal and social control professionals, functionaries, and participants. The chapters in the collection bring to the foreground the distinctive contributions that ethnographic and ethnomethodologically-informed studies have to offer research on law and social control from theoretical, methodological, and substantive viewpoints.The discussions address a usefully broad and timely variety of themes, including management of the media by prosecutors in the famous Mike Tyson rape case; celebrity stalking and its social control; community protection strategies and legislation for high-risk sex offenders; probation officers' use of technology to "monitor" domestic violence offenders; how contemporary immigration rules-in-practice impact the immigration status of skilled professionals; bureaucratic decision-making by federal housing officers; police methods of interrogating suspects through an interpreter; how juvenile courts respond to troublesome youths; Self-change treatment programs for violent offenders in prison; and, how jail inmates construct parenthood behind bars. The collection emphasizes the need to consider the organizationally and institutionally specific features and competencies that comprise the legal and social control work under investigation and allows for a deeper appreciation of the practical terms through which people involved in this work make their activities meaningful, carry out their tasks, and organize their interactions.
Includes bibliographical references.
Description based on print version record.
Keywords: Crime prevention; Crime -- Sociological aspects; Social control; Justice, Administration of -- Social aspects; Crime & criminology; Law -- General; Social Science -- Criminology